Students’ online educational engagement and social relationship through emerging technologies during Covid-19 pandemic - Emmalene Maldepena; Sherijane Tamblik (CV Rezki Media, 2023)
The advancements in educational technology have proven to be useful during remote learning amidst pandemic, especially in connecting with social groups. The study aimed to relate students’ online educational engagement and social relationships through emerging technologies during the Covid-19 outbreak. Following a descriptive-correlational research design, this study involved one hundred twenty (120) regular third-year Mindanao State University-General Santos City, students. They were officially enrolled during the first semester of 2021-2022. The study used a researcher-made survey questionnaire and interview guide questions, checked, and validated by the experts, to gather the needed data in the study. The weighted mean and Pearson Product-Moment Correlation Coefficient was used to analyze and identify the study results. Findings revealed that the students use social media such as Messenger, Google Meet, Facebook, emails, and other online platforms to communicate with their family, friends, and teachers. Also, it was found that students form social relationships through consistent communication and positive communication. The results indicated that the online educational engagement of the students significantly influences their social relationships. This study recommended that the Faculty of the College of Education, Bachelor of Elementary Education, Mindanao State University-General Santos City, may use other online tools such as Viber for online education to enhance students’ online learning further.